Electronic speckle pattern surface contouring using optical fibres and wavelength modulation of laser diodes - Tatam, Ralph P.; Davies, Jeremy C.; Buckberry, Clive H.; Jones, Julian D. C. (International Society for Optical Engineering; 1999, 1990)
The incorporation of laser diodes and monomode fibre optics into an Electronic Speckle Pattern Interferometer (ESPI) has led to the development of a novel holographic surface contouring system. Height contours are obtained by switching between two laser wavelengths. Contour intervals from 0.5-5 mm have been generated by modulating the injection current of a single laser diode source and are demonstrated on an automotive disc brake hub.